Managing animal wellbeing: a preliminary survey of pig farmers. Issue 6 (15th April 2014) - Wilson, RL; Holyoake, PK; Cronin, GM; Doyle, RE
<x xml:space="preserve">Abstract</x> Objectives To gather information on producers' perceptions and management strategies towards the detection, alleviation of pain and management of sick, injured and heat‐stressed pigs. Methods A total of 16 Victorian pig farmers completed a face‐to‐face questionnaire consisting of 9 open and 26 closed questions regarding their detection and management of sick, injured and heat‐stressed pigs and their perceptions of pigs' tolerance to pain. Results We identified 15 behavioural and physiological indicators of pain and heat stress. Treatment records were kept more often for weaned progeny and lactating sows than for piglets and mated sows. Most producers felt that pigs suffered little pain from routine husbandry procedures and that pain relief was not warranted in those situations. Castration at 10 days of age was the only procedure considered by producers to be very painful. There were inconsistencies in approaches to treating pigs in three case studies of animals with sickness or injury of varying severity. Meloxicam was stated as the most common anti‐inflammatory drug used on‐farm. A small proportion of farmers incorrectly identified antibiotics as anti‐inflammatory drugs. All producers had at least one cooling system in place for preventing heat stress in pigs. Conclusions The farmers in this survey group generally relied on behavioural changes in pigs to signal pain and heat stress. Although producers kept treatment records and used hospital pens for compromised pigs, our results suggest that the monitoring of pigs' recovery could be improved. Producers generally have a good understanding of the use of anti‐inflammatory drugs to aid recovery of pigs.